2020
DOI: 10.1155/2020/4736476
|View full text |Cite
|
Sign up to set email alerts
|

PL-7 Antisynthetase Syndrome in Association with Sjögren’s, Systemic Lupus Erythematosus, and Rheumatoid Arthritis

Abstract: We present a rare case of PL-7 antisynthetase syndrome (ASS) in association with Sjögren’s, systemic lupus erythematosus (SLE), and seropositive rheumatoid arthritis (RA). Initially, the patient was diagnosed with Sjögren’s followed by Sjögren’s/SLE overlap and then Sjögren’s/SLE/RA overlap. She was eventually diagnosed with Sjögren’s/SLE/RA overlap with PL-7 ASS with interstitial lung disease (ILD). ILD was discovered after complaints of pleuritic chest pain with subsequent workup with coronary computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…According to Kurata et al, aortic aneurysm is a rare cardiac complication of lupus [ 24 , 29 ]. Diagnosis and treatment of cardiopulmonary involvement in CTD may be delayed due to its ambiguity of presenting symptoms and is associated with increased morbidity and mortality and poor survival [ 30 ]. Therefore, careful attention should be paid to identify patients with CTD to identify features of cardiopulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kurata et al, aortic aneurysm is a rare cardiac complication of lupus [ 24 , 29 ]. Diagnosis and treatment of cardiopulmonary involvement in CTD may be delayed due to its ambiguity of presenting symptoms and is associated with increased morbidity and mortality and poor survival [ 30 ]. Therefore, careful attention should be paid to identify patients with CTD to identify features of cardiopulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Hervier and Lambert et al reported an interesting rare case of overlap syndrome with PL-7 ASS, Sjogren's, systemic lupus erythematosus and RA with evolving symptoms over time. 8,[13][14][15] Anti-synthetase syndrome has often been reported in overlap with polymyositis, dermatomyositis, systemic sclerosis, Sjogren's and RA.…”
Section: Discussionmentioning
confidence: 99%